2021
DOI: 10.1037/spq0000427
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation and use of the Multidimensional Test Anxiety Scale (MTAS).

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Despite the inconsistency in approaches used to categorise groups of high- and low-test anxiety, four studies ( Beidel and Turner 1988 ; Beidel et al 1994 ; Herzer et al 2014 ; King et al 1995 ), showed that persons scoring highly on continuous measures of test anxiety met diagnostic thresholds for an anxiety disorder. One study ( von der Embse et al 2021 ) showed students scoring high on a continuous measure of test anxiety were at an elevated risk of developing generalized anxiety disorder (GAD) and panic disorder (PD) using pre-existing cut points on measures on the Revised Child Anxiety and Depression Scale ( Chorpita et al 2005 ). In addition, three studies ( King et al 1995 ; Warren et al 1996 ; Weems et al 2010 ) showed that persons scoring high on continuous measures of test anxiety also reported higher symptoms of emotional disorders (i.e., anxiety and depression).…”
Section: Defining Test Anxietymentioning
confidence: 99%
“…Despite the inconsistency in approaches used to categorise groups of high- and low-test anxiety, four studies ( Beidel and Turner 1988 ; Beidel et al 1994 ; Herzer et al 2014 ; King et al 1995 ), showed that persons scoring highly on continuous measures of test anxiety met diagnostic thresholds for an anxiety disorder. One study ( von der Embse et al 2021 ) showed students scoring high on a continuous measure of test anxiety were at an elevated risk of developing generalized anxiety disorder (GAD) and panic disorder (PD) using pre-existing cut points on measures on the Revised Child Anxiety and Depression Scale ( Chorpita et al 2005 ). In addition, three studies ( King et al 1995 ; Warren et al 1996 ; Weems et al 2010 ) showed that persons scoring high on continuous measures of test anxiety also reported higher symptoms of emotional disorders (i.e., anxiety and depression).…”
Section: Defining Test Anxietymentioning
confidence: 99%
“…It is widely considered that test anxiety is multidimensional comprising affective-physiological and cognitive components. In the present study we used a four-factor model of test anxiety von der Embse et al, 2021). There were two affective-physiological factors, namely tension (feelings of unpleasant emotions associated with anxiety) and physiological indicators of anxiety (the perception of autonomic arousal associated with anxiety).…”
Section: Test Anxietymentioning
confidence: 99%
“…The relationship between test anxiety, mental health, and wellbeing, has received less attention in the research literature. Nonetheless, studies have shown that highly test anxious students show greater symptoms of anxiety disorders (Putwain, Stockinger, et al, 2021;von der Embse et al, 2021;Weems et al, 2015) and meet diagnostic thresholds for anxiety disorders (Herzer et al, 2014;King et al, 1995). In addition, after accounting for concurrent relations, test anxiety has been shown to predict an increased risk for lower wellbeing (Steinmayr et al, 2015) and subsequent emotion disorders (Putwain, Gallard, et al, 2021).…”
Section: Test Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Putwain et al [7] reported that MTAS has strong internal consistency (ωs = 0.85-0.91), factorial validity (items loading on target factors λs = 0.46-0.92), and predictive. Also, von der Embse et al [37] reported adequate confirmatory factor analysis of the instrument supporting the construct validity of MTAS. In the current study, we obtained internal consistency values for the four subscales of MTAS; (α = 0.61-0.73); and total test anxiety (α = 0.86).…”
Section: Instrumentsmentioning
confidence: 87%